Волонтерська допомога у створенні засобів індивідуального захисту та технічного оснащення військовослужбовців у зоні АТО - Юрова, Тетяна Миколаївна; Yurova, Tatiana N. (Східноєвропейський національний університет імені Лесі Українки, 2015)
В умовах АТО виникає необхідність екіпірування та забезпечення технікою ЗСУ. Держава не завжди в змозі задовольнити всі потреби армії й у такому випадку на допомогу приходять волонтери, котрі не тільки збирають кошти, а й постають у якості раціоналізаторів, винахідників і виробників. Їхню роль для ЗСУ розглянуто в публікації. In the context of the ATO in the east of the country it is urgent need to provide equipment and technology to the military. Unfortunately, the state does not always have the opportunity to meet all the needs of the army, and in this case, the army has to come to the aid of volunteer organizations. That is why their role in the Ukrainian army is considered in the article. After all, they not only raise funds for the necessary things for military operations, but often themselves acting as producers and suppliers of equipment, ammunition, personal protective equipment, monitoring tools for transportation vehicles. Organized exhibitions and numerous photos of modernized equipment by volunteers directly from the combat zone is a proof of their work. The purpose of this publication is the analysis of the achievements of volunteers in the manufacture of personal protective equipment for fighters and improvements for future use in ATO.
Volunteer Assistance in Creating Personal Protective and Technical Equipment for Troops in the Area of ATO
Keywords: volunteers; equipment; technology; engineering; military; ATO; волонтери; АТО; спорядження; технології; техніка; армія